Intervention study of finger-movement exercises and finger weight-lift training for improvement of handgrip strength among the very elderly - Xue-Ping Chen; You-Mei Lu; Ju Zhang (Elsevier, 2014)
Objectives: To examine the effects of finger-movement exercises and finger weight-lift training on handgrip strength and Activities of Daily Living Scale (ADLS) values. Methods: A total of 80 very elderly adults (aged ≥80 years) were assigned to either an intervention group (n = 40) or a control group (n = 40). Subjects in the intervention group performed finger-movement exercises and weight-lift training for a period of 3 months, while subjects in the control group received no intervention, and were unaware of the interventions received in the other group. Results: After completing 3 months of finger-movement exercises and weight-lift training, the average handgrip strength of the 40 participants in the intervention group had increased by 2.1 kg, whereas that in the control group decreased by 0.27 kg (P < 0.05). After receiving intervention, the number of subjects in the intervention group with an ADLS score >22 points decreased by 7.5% (P < 0.05, vs. pre-intervention). Conclusions: The combined use intervention with finger-movement exercises and proper finger weight-lift training improved the handgrip strength and ADLS values of very elderly individuals. These rehabilitation exercises may be used to help the elderly maintain their self-care abilities.